Search for massive colored scalars in four-jet final states in √ s = 7 TeV proton–proton collisions with the ATLAS detector - Anduaga, Xabier Sebastián (2011)
A search for pair-produced scalar particles decaying to a four-jet final state is presented. The analysis is performed using an integrated luminosity of 34 pb−1 recorded by the ATLAS detector in 2010. No deviation from the Standard Model is observed. For a scalar mass of 100 GeV (190 GeV) the limit on the scalar gluon pair production cross section at 95% confidence level is 1 nb (0.28 nb). When these results are interpreted as mass limits, scalargluons (hyperpions) with masses of 100 to 185 GeV (100 to 155 GeV) are excluded at 95% confidence level with the exception of a mass window of width about 5 GeV (15 GeV) around 140 GeV.